2006
DOI: 10.1021/ol062661s
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydrogenation of α-Chloro Aromatic Ketones Catalyzed by η6-Arene/TsDPEN−Ruthenium(II) Complexes

Abstract: Asymmetric hydrogenation of various alpha-chloro aromatic ketones with Ru(OTf)(TsDPEN)(eta6-arene) (TsDPEN = N-(p-toluenesulfonyl)-1,2-diphenylethylenediamine) produces the chiral chlorohydrins in up to 98% ee. This reaction can be conducted even on a 206-g scale. The hydrogenation of an alpha-chloro ketone with a phenol moiety has been utilized for the synthesis of (R)-norphenylephrine without protection-deprotection operations. [reaction: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(73 citation statements)
references
References 25 publications
1
72
0
Order By: Relevance
“…[2,4] Recently it was discovered that these amido complexes can be easily converted into catalysts for direct hydrogenation. [5][6][7][8][9] The key insight is that protonation of 16e diamido complexes generates cationic derivatives that are sufficiently electrophilic to activate H 2 directly. [10,11] Upon exposure to H 2 , these cationic complexes convert to amino hydrides that in turn reduce ketones and imines following the pathway for traditional TH catalysis (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[2,4] Recently it was discovered that these amido complexes can be easily converted into catalysts for direct hydrogenation. [5][6][7][8][9] The key insight is that protonation of 16e diamido complexes generates cationic derivatives that are sufficiently electrophilic to activate H 2 directly. [10,11] Upon exposure to H 2 , these cationic complexes convert to amino hydrides that in turn reduce ketones and imines following the pathway for traditional TH catalysis (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that methanol has been successfully used in the asymmetric hydrogenation of ketones by Noyori and coworkers, [9] we first examined the asymmetric hydrogenation Scheme 1. Asymmetric hydrogenation of quinoline 2 a catalyzed by Ru/ Ts-dpen catalysts.…”
mentioning
confidence: 99%
“…[8] Recently, Noyori and co-workers reported that chiral h 6 -arene/Ntosylethylenediamine-Ru II complexes (which are known as excellent catalysts for asymmetric transfer hydrogenation, for example Ru/Ts-dpen) can be used for the asymmetric hydrogenation of prochiral ketones under slightly acidic conditions. [9] Inspired by this important breakthrough and following our continued pursuit of developing effective and environmentally benign catalyst systems for asymmetric hydrogenations, [10] herein we report a practical and efficient catalyst system of Ru/Ts-dpen in [BMIM]PF 6 (BMIM = 1-nbutyl-3-methylimidazolium) for the enantioselective hydrogenation of quinolines (Scheme 1).…”
mentioning
confidence: 99%
“…The conversions were determined by GC analysis. Enantiomeric excesses were determined by optical rotation measurements [22,23]. As shown in Table 1, for various ketones, including 2-substituted, electron-rich, and electron-deficient variants, the catalyst afforded good to excellent conversions and enantioselectivities.…”
Section: Resultsmentioning
confidence: 99%